Risk Assessment in the UK Health and Safety System: Theory and Practice - Karen Russ (Elsevier, 2010)
In the UK, a person or organisation that creates risk is required to manage and control that risk so that it is reduced 'So Far As Is Reasonably Practicable' (SFAIRP). How the risk is managed is to be determined by those who create the risk. They have a duty to demonstrate that they have taken action to ensure all risk is reduced SFAIRP and must have documentary evidence, for example a risk assessment or safety case, to prove that they manage the risks their activities create. The UK Health and Safety Executive (HSE) does not tell organisations how to manage the risks they create but does inspect the quality of risk identification and management. This paper gives a brief overview of where responsibility for occupational health and safety lies in the UK, and how risk should be managed through risk assessment. The focus of the paper is three recent major UK incidents, all involving fatalities, and all of which were wholly avoidable if risks had been properly assessed and managed. The paper concludes with an analysis of the common failings of risk assessments and key actions for improvement.